Kapitan keling waqf land development: Issues and challenges - Ismail, Che Zuina; Bakar, Marina Abu; Ismail, Sukriah; Ramli, Noor Asyimah (Linguistics and Culture Review, 2021)
Kapitan Keling waqf land, which was endowed in 1801, is located in the heart of Georgetown, Penang. The Kapitan Keling Mosque has been the focus of this development. At the initial stage, this waqf land was in the form of land assets then developed with several row units of shop houses that suited the concept and environment at the time. Furthermore, the management of this waqf land has been taken over by the Penang Islamic Religious Council (MAINPP) with its creation, a more planned development concept and strategy has been implemented. Throughout the development of Kapitan Keling waqf land, many challenges have been overcome. The permanence of Kapitan Keling waqf until today is a manifestation of his success in overcoming various challenges. However, current developments and development efforts undertaken at present lead to various new challenges. Therefore, this study aims to study and analyze the issues and challenges of Kapitan Keling waqf land development. This study uses a qualitative design. Data were collected through documents and interviews with informants at MAINPP. These data were then analyzed using a content analysis approach.